Weibull Analysis of Charpy Impact Test in Short Date Palm Fiber Reinforced Epoxy Composite - Boulebnane, Adel; Djeghader, Djamel; Tioua, Tahar (Periodica Polytechnica Civil Engineering, 2024)
This study is a contribution to the valorization of natural ﬁber, which improve sustainability by substituting non-renewable raw materials by natural renewable resources. In this work, the fabrication and investigation of composite date palm fiber reinforced epoxy (DPFE) and compare it with an unreinforced epoxy resin (ER). One volume fraction, 10% by volume, of short date palm fiber (2–3 cm in length) was considered. A dynamic impact characterization of DPFE and ER are obtained by using the Charpy impact test. The Williams method based on the principle of linear elastic fracture mechanics was used to deduce the impact toughness of composite. The experimental results were statistically analyzed by using the two and three parameter Weibull distribution in order to evaluate the survival/reliability probability of the studied composite. It is found that the DPFE composite has better properties than the ER material in Charpy impact test.